Nonresonant optical control of a spinor polariton condensate - Askitopoulos, A. (2017)
We investigate the spin dynamics of polariton condensates spatially separated from and effectively confined by the pumping exciton reservoir. We obtain a strong correlation between the ellipticity of the nonresonant optical pump and the degree of circular polarization (DCP) of the condensate at the onset of condensation. With increasing excitation density we observe a reversal of the DCP. The spin dynamics of the trapped condensate are described within the framework of the spinor complex Ginzburg-Landau equations in the Josephson regime, where the dynamics of the system are reduced to a current-driven Josephson junction. We show that the observed spin reversal is due to the interplay between an internal Josephson coupling effect and the detuning of the two projections of the spinor condensate via transition from a synchronized to a desynchronized regime. These results suggest that spinor polariton condensates can be controlled by tuning the nonresonant excitation density offering applications in electrically pumped polariton spin switches.